2006
DOI: 10.1158/0008-5472.can-06-0325
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibition Induces Apoptosis Signaling via Death Receptors and Mitochondria in Hepatocellular Carcinoma

Abstract: Inhibition of cyclooxygenase (COX)-2 elicits chemopreventive and therapeutic effects in solid tumors that are coupled with the induction of apoptosis in tumor cells. We investigated the mechanisms by which COX-2 inhibition induces apoptosis in hepatocellular carcinoma (HCC) cells. COX-2 inhibition triggered expression of the CD95, tumor necrosis factor (TNF)-R, and TNF-related apoptosis-inducing ligand (TRAIL)-R1 and TRAIL-R2 death receptors. Addition of the respective specific ligands further increased apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 45 publications
7
121
0
2
Order By: Relevance
“…PGE 2 is the prostaglandin that is abundantly present in HCC. Studies have established the important role of the PGE 2 synthesis pathway as a potential target for the treatment and/ or prevention of HCC [8,9] . PGE 2 exerts its biological activities primarily via G-protein-coupled prostaglandin receptors (EP [1][2][3][4] ), which belong to the highly conserved superfamily of www.nature.com/aps Jin J et al Acta Pharmacologica Sinica npg 7-transmembrane-spanning proteins.…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 is the prostaglandin that is abundantly present in HCC. Studies have established the important role of the PGE 2 synthesis pathway as a potential target for the treatment and/ or prevention of HCC [8,9] . PGE 2 exerts its biological activities primarily via G-protein-coupled prostaglandin receptors (EP [1][2][3][4] ), which belong to the highly conserved superfamily of www.nature.com/aps Jin J et al Acta Pharmacologica Sinica npg 7-transmembrane-spanning proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we and others demonstrated that partial hepatectomy 7 induced COX-2 in hepatocytes and contributed to the progression of cell cycle after partial hepatectomy. 8,9 In addition to liver regeneration after partial hepatectomy or hepatotoxic agents, expression of COX-2 has been detected in animal models of cirrhosis, 10 in human hepatoma cell lines, 11,12 after hepatitis B virus and hepatitis C virus infection, 13,14 and in human HCC. 15 High levels of COX-2-derived prostaglandin E 2 (PGE 2 ) lead to a decrease in apoptosis, a modulation of the immune system and a stimulation of cell migration, proliferation, and angiogenesis.…”
mentioning
confidence: 99%
“…FR122047, a COX-1 inhibitor induced apoptosis in MCF-7 breast cancer cells by a mechanism independent of its ability to suppress PGs synthesis because exogenous PGE 2 had no effect on FR122047-induced apoptosis in MCF-7 cells (data not shown). Celecoxib and other NSAIDs showed that drug-induced apoptosis could be caused through intrinsic pathway by cytochrome c release from mitochondria and activation of caspase-9 as well as extrinsic pathway by activation of caspase-8 (34)(35)(36). FR122047-treated MCF-7 cells exhibited a rapid down-regulation of Bcl-2, resulting in an increase in the Bax/Bcl-2 ratio.…”
Section: Discussionmentioning
confidence: 99%